The association between oral health literacy and oral health behaviors in North Korean defectors: a cross-sectional study - Han-A Cho; Ae-Jung Im; Yu-Ri Sim; Han-Byoel Jang; Hee-Jung Lim (BMC, 2020)
Abstract Background The present study aimed to investigate the association between oral health literacy and oral health behaviors among North Korean defectors. Methods This study involved the collection of self-reported questionnaires from 123 North Korean defectors visited a dental clinic that offered complimentary services, to receive dental treatment in a metropolitan area of South Korea from December 2017 to April 2018. Oral health literacy was measured with the Test of Korean Functional Health Literacy in Dentistry (TOKFHLiD), which consists of 30 items concerning verbal oral health literacy and 42 items concerning functional oral health literacy (28 items for reading comprehension and 14 items for numeracy). In addition, the questionnaire contains 15 and 14 items related to demographic characteristics and oral health behaviors (interest, lifestyle, diet, prevention), respectively, for a total of 101 items. Results The mean oral health literacy score was 44 (out of a maximum possible score of 72). Oral health literacy and oral health behaviors were positively correlated (r = 0.526, P < 0.001), and oral health literacy also had a significant effect on oral health behaviors (Beta = 0.26, 95% CI: 0.04-0.33). However, although functional oral health literacy had a significant effect on oral health behaviors (Beta = 0.20, 95% CI: 0.01-0.43), verbal oral health literacy did not (Beta = 0.13, 95% CI: − 0.06-037). Conclusions Educational interventions are needed to improve oral health literacy, and thus oral health behaviors, as a part of the health promotion measures undertaken to facilitate the stable adjustment of North Korean defectors in South Korean society.